2003
DOI: 10.1080/0143116021000044814
|View full text |Cite
|
Sign up to set email alerts
|

On the longitude dependence of total ozone trends over middle-latitudes

Abstract: It has recently been observed that the total ozone trends derived from certain geographical regions such as the Mediterranean and Athens (Greece) show similar values to those derived from the 40 ‡ N zonal averaged column ozone data. In this Letter, the total ozone concentration, collected by the Total Ozone Mapping Spectrometer (TOMS) flown on Nimbus-7 and Meteor-3 during the time-the Mediterranean, Athens (Greece) and Srinagar (India), is analysed. Further, the harmonic analysis performed on total ozone time-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 91 publications
(26 citation statements)
references
References 15 publications
0
25
0
1
Order By: Relevance
“…Indeed, many previous studies have demonstrated the important role of planetary waves in modulating ZAO variations (e.g. Peters and Entzian 1999;Peters et al 2008;Efstathiou et al 2003;Hio and Yoden 2004;Grytsai et al 2005;Gabriel et al 2011;Ialongo et al 2012;Zhang et al 2015) and have proposed that the planetary waves of tropospheric origin could affect TCO through tropopause height modulations and stratosphere-troposphere exchange processes. Nevertheless, whether and to what extent planetary wave changes exert an influence on the zonally asymmetric TCO trend in the past 30 years remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, many previous studies have demonstrated the important role of planetary waves in modulating ZAO variations (e.g. Peters and Entzian 1999;Peters et al 2008;Efstathiou et al 2003;Hio and Yoden 2004;Grytsai et al 2005;Gabriel et al 2011;Ialongo et al 2012;Zhang et al 2015) and have proposed that the planetary waves of tropospheric origin could affect TCO through tropopause height modulations and stratosphere-troposphere exchange processes. Nevertheless, whether and to what extent planetary wave changes exert an influence on the zonally asymmetric TCO trend in the past 30 years remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Reid et al, 1994;Gernandt et al, 1995;Efstathiou et al, 2003;Cracknell and Varotsos, 1994Tzanis and Varotsos, 2008;Alexandris et al, 1999). Temperature dependent measurements of diffusion coefficients for HCl, CH 3 OH, HCOOH and CH 3 COOH in ice, as studied in recent measurements (Livingston et al, 2002;Nehme, 2006) show that their D o -values differ by several orders of magnitude.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, such particles, apart from their involvement to various mechanisms in the lower troposphere (Asimakopoulos et al, 1992;Cartalis and Varotsos, 1994;Ferm et al, 2005Ferm et al, , 2006) also contribute to radiative forcing as well as to chemical conversions in the upper troposphere where they exist in form of cirrus clouds and contrails. Since the rates of heterogeneous chemical conversions depend on both surface and bulk…”
Section: Introductionmentioning
confidence: 99%
“…The large vertical temperature gradients both above and below the tropical tropopause act as a strong constraint on the size of the tropopause height changes that can be caused by predominantly tropical modes of variability (such as El Nino/Southern Oscillation -ENSO). In contrast, ozone-and GHG-induced cooling of the stratosphere tend to be largest in high latitudes at both hemispheres (Cortesi et al, 2007;Efstathiou et al, 2003;Gernandt et al, 1995;Kondratyev et al, 1994;Sausen and Santer, 2003).…”
Section: Introductionmentioning
confidence: 99%